Apa yang Menjadikan Remaja Indonesia Bangga Terhadap Bangsanya? - Nurva Dillatul Vatin; Sartana Sartana (Universitas Andalas, 2023)
A person's pride in his nation is the main pillar to support the existence and sustainability of the country. Young Indonesians growing up in the era of digital democracy tend to develop a distinctive national identity and source of national pride compared to previous generations. Unfortunately, various things which become a source of pride for Indonesian adolescents towards their nation are rarely explored. This study aimed to identify various sources of national pride for adolescents in Indonesia. Around 385 respondents (aged 18 – 21 years), consisting of 313 females and 72 males involved in the study. The data in this study were collected using an open questionnaire containing one question,